2011
DOI: 10.1542/peds.2010-1623
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Kimura Disease With Intravenous Immunoglobulin

Abstract: Kimura disease is an uncommon chronic inflammatory condition of unknown etiology and is characterized by painless subcutaneous nodules, usually affecting the head and neck, eosinophilia, and markedly elevated immunoglobulin E levels. Several reports have described the main modalities of treatment; both corticosteroids and surgery have provided good results, but occasionally corticosteroids cannot be tapered as the disease flares up. We report here the case of an 8-year-old boy diagnosed with Kimura disease who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…The therapeutic regimen for KD is difficult to assess in the literature, as most data are reported in case reports or short series [8,9,24,25,26]. In patients with a solitary cutaneous lesion and no systemic signs, surgical excision was proposed in first intention with 100% of CR and 60% of relapse.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic regimen for KD is difficult to assess in the literature, as most data are reported in case reports or short series [8,9,24,25,26]. In patients with a solitary cutaneous lesion and no systemic signs, surgical excision was proposed in first intention with 100% of CR and 60% of relapse.…”
Section: Discussionmentioning
confidence: 99%
“…A dose of 5 mg/kg/d was effective, but, in most cases, the lesions recurred upon cessation of therapy [17]. Intravenous immunoglobulin (IVIG) was used in one patient as a steroid-sparing agent, and he remained disease free more than 6 years after follow-up [18]. Oral pentoxifylline has been reported to be effective in one patient with Kimura's disease; however, the lesions relapsed after discontinuation of therapy [19].…”
Section: Discussionmentioning
confidence: 99%
“…Due to intermittent dependency on corticosteroid, immunoglobulin therapy was tried for the treatment of Kimura's disease as a steroidsparing therapy. 3 Recently, a study showed the efficacy of tacrolimus on Kimura's disease. 10 The 2 previously reported patients with IgA nephropathy were treated with corticosteroids and showed significant decrease in proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…2 Additional characteristics include marked peripheral eosinophilia and elevated immunoglobulin E (IgE) levels. 3 Kidney involvement occurs in 12-16% of patients with Kimura's disease, and 60-78% of kidney involvement is in the form of nephrotic syndrome. 4,5 Although various types of glomerulonephritis, such as membranous glomerulonephritis, mesangial proliferative glomerulonephritis, minimal-change disease, focal segmental glomerulosclerosis, and diffuse proliferative glomerulonephritis, have been reported to be associated with Kimura's disease, 6 only 2 cases of Immunoglobulin A (IgA) nephropathy have been reported in Kimura's disease to date; thus, the association between these 2 diseases remains unclear.…”
Section: Introductionmentioning
confidence: 99%